An exploration and practice of curriculum ideology and politics based on positive psychology in the teaching of Introduction to Nursing (积极心理学在《护理学导论》课程思政教学中的实施策略研究) - JU Yaya (琚亚亚) (Association of Integrative Nursing, 2023)
Objective To explore the implementation strategy and teaching effect of curriculum ideology and politics based on positive psychology in the teaching of Introduction to Nursing. Methods The course content of positive virtues and personality, ideological and political elements and introduction to nursing was condensed, integrated, designed, and implemented. The Nursing Professional Recognition Questionnaire was used to evaluate the effect. A total of 121 nursing students of batch 2022 were recruited. The teaching evaluation score in students of batch 2021 was compared with that of students of batch 2021. Results The total scores of professional identity, occupational self-concept, job retention benefits and exit risk, social comparison and self-reflection, and autonomy dimension of career choice were higher than the norm, and the social persuasion was lower than the norm, and the difference was statistically significant (P＜0. 05). The teaching evaluation score in nursing students of batch 2022 was higher than that of students of batch 2021, and the difference was statistically significant (P＜0. 05). Conclusion The ideological and political teaching of the Introduction to Nursing course guided by the concept of positive psychology is conducive to cultivating students' sense of professional identity and professional belonging, and improving teaching satisfaction. (目的 探讨积极心理学在《护理学导论》课程思政教学中的实施策略及教学效果。方法 将积极美德与人格、思政要素及护理学导论的课程内容进行凝练、融合、设计, 并进行教学实施。选取121名2022级护理本科生为研究对象, 采用护理本科生专业认同调查问卷进行效果评价, 并将2022级护理本科生的评教满意度得分与 2021级护理本科生进行对比。结果 实施教学后, 护理本科生专业认同调查问卷的职业认同总分、职业自我概念、留职获益与离职风险、社会比较与自我反思、职业选择的自主性维度得分高于常模, 社会说服维度低于常模, 差异有统计学意义(P＜0. 05)。实施教学后, 2022级护理本科生的评教满意度得分高于2021级, 差异有统计学意义(P＜0. 05)。结论 积极心理学理念引导下的《护理学导论》课程思政教学有利于培养护理本科生的专业认同感与职业归属感, 提升教学满意度。)